Locals' perceptions towards the impacts of tourism and the importance of local engagement: A comparative study of two islands in Malaysia - Nejati, Mehran; Mohamed, Badaruddin; Omar, Shida Irwana (2014)
Th is study investigates the perception of locals residing on two touristic islands in Malaysia about the economic, social, environmental and cultural impacts of tourism development. Additionally, the importance of local engagement in tourism development was also investigated from the perspective of residents. A total of 371 responses were collected (183 local residents on Perhentian island and 188 local residents on Redang island). Results of the study reveal that while residents on both islands perceive the highest environmental impacts of tourism on water quality, wildlife, and air quality, the environmental impacts are perceived to be lower for residents of Redang island than in Perhentian island. Besides the detrimental impacts of tourism on environment, majority of the locals perceive the positive economic, social and cultural impacts of tourism to be larger than its negative impacts. Additionally, the study found that residents perceived the engagement of locals in tourism development to be important. Th e fi ndings of this study provide invaluable implications to tourism development managers and policy makers.